2020
DOI: 10.1177/1055665620954090
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Craniofacial Characteristics in Patients With 14Q22.1-Q22.2 Deletion: A Case Series

Abstract: This case series is a follow-up report focusing on dental and facial characteristics in patients with a rare microdeletion in chromosome 14q22.1-q22.2. Usually, these patients have severe ocular, brain, and digital abnormalities. However, this case series shows that clinical presentation can be mild. Four relatives spanning 3 generations were diagnosed with a familial autosomal dominant 2.79 Mb microdeletion in chromosome 14q22.1-q22.2. Genetic screening was done by the Bacterial Artificial Chromosome array-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In addition, the TP63 gene has been found to be associated with SD in the presence of other abnormalities [65,66]. Recently, autosomal dominant SD has been associated with a microdeletion of 2.79 Mb at chr14q22-q22.2 in four affected members of a three-generation family with limb defects (syndactyly and polydactyly) along with other disorders, such as developmental delay and facial defects [67]. Recently, it has been reported that children with SD and prolonged heartrate-corrected QT (QTc) interval have more multisystem diseases and electrocardiographic abnormalities [68].…”
Section: Some Excluded Types Of Syndactyly and Underlying Genetic Fac...mentioning
confidence: 99%
“…In addition, the TP63 gene has been found to be associated with SD in the presence of other abnormalities [65,66]. Recently, autosomal dominant SD has been associated with a microdeletion of 2.79 Mb at chr14q22-q22.2 in four affected members of a three-generation family with limb defects (syndactyly and polydactyly) along with other disorders, such as developmental delay and facial defects [67]. Recently, it has been reported that children with SD and prolonged heartrate-corrected QT (QTc) interval have more multisystem diseases and electrocardiographic abnormalities [68].…”
Section: Some Excluded Types Of Syndactyly and Underlying Genetic Fac...mentioning
confidence: 99%